Efektivitas Pelatihan Konseling Al Qur’an dalam Meningkatkan Resiliensi Mahasiswa - Ahmad Razak; M. Ahkam Alwi; Muhrajan Piara (Jurnal Psikologi TALENTA, 2022)
This study examined the effectiveness of Al-Quran Counseling training in improving the resilience of students. This study aimed to determine differences in the resilience of students before and after al-Quran counseling training. There were 40 students as participants in this study. Purposive sampling was used in this study to acquire the participants. The research program was quasi experiment one group pretest-posttest design. Data analysis was performed using paired samples t test. The results showed that there are differences in the resilience of students before and after al-Quran Counseling training.